2021
DOI: 10.1371/journal.pone.0238669
|View full text |Cite
|
Sign up to set email alerts
|

Protected areas network is not adequate to protect a critically endangered East Africa Chelonian: Modelling distribution of pancake tortoise, Malacochersus tornieri under current and future climates

Abstract: While the international pet trade and habitat destruction have been extensively discussed as major threats to the survival of the pancake tortoise (Malacochersus tornieri), the impact of climate change on the species remains unknown. In this study, we used species distribution modelling to predict the current and future distribution of pancake tortoises in Zambezian and Somalian biogeographical regions. We used 224 pancake tortoise occurrences obtained from Tanzania, Kenya and Zambia to estimate suitable and s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Protected areas (PAs), as one of the leading conservation tools for biodiversity, are mainly associated with potential failure to protect species against climate and landscape change [19,[86][87][88][89][90][91][92][93][94][95][96]. While some studies have shown that PAs remained suitable climates, facilitated the range expansion and colonization of species, and decreased historical loss [89,[97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…Protected areas (PAs), as one of the leading conservation tools for biodiversity, are mainly associated with potential failure to protect species against climate and landscape change [19,[86][87][88][89][90][91][92][93][94][95][96]. While some studies have shown that PAs remained suitable climates, facilitated the range expansion and colonization of species, and decreased historical loss [89,[97][98][99][100].…”
Section: Discussionmentioning
confidence: 99%
“…In total, 300 models were generated and evaluated based on AUC and TSS. The ensemble was generated from models with AUC values greater than the mean plus half a standard deviation or models with TSS values greater than the mean plus half a standard deviation [ 67 ]. A threshold model was also created based on the TSS cut-off value.…”
Section: Methodsmentioning
confidence: 99%
“…We sampled the tortoises opportunistically and record the evidence of predation at six sites and out-of-crevice activities at three. The names and locations of the sites have been withheld to protect the critically endangered pancake tortoise from illegal harvest (Eustace et al, 2021).…”
Section: Résumémentioning
confidence: 99%